Evangelical Christianity and democracy in Latin America - Freston, Paul (Evangelical Christianity and democracy in the Global South., 2008)
In Latin America, evangelical Protestantism poses an increasing challenge to Catholicism's long-established religious hegemony. At the same time, the region is among the most generally democratic outside the West, despite often being labeled as 'underdeveloped.' Scholars disagree whether Latin American Protestantism, as a fast-growing and predominantly lower-class phenomenon, will encourage a political culture that is repressive and authoritarian, or if it will have democratizing effects. Drawing from a range of sources, Evangelical Christianity and Democracy in Latin America provides case studies of five countries: Brazil, Peru, Mexico, Guatemala, and Nicaragua. The contributors, mainly scholars based in Latin America, bring first hand-knowledge to their chapters. The result is a work that explores the relationship between Latin American evangelicalism and politics, its influences, manifestations, and prospects for the future. --From publisher's description.